AMAZING ANTIMICROBIAL AND WOUND HEALING POTENTIAL OF ACACIA CATECHU BARK EXTRACTS- A REVIEW - TIWARI, ARCHANA; TIWARI, AVINASH (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Plants are not only the source of food, oxygen, and shelter, but the same are also a potential foundation of medicines. Many natural and plant-derived antimicrobial and wound healing compounds have been recognized. In the present review, we have studied the main bioactive components of Acacia catechu with their medicinal roles. Most of these bioactive components are secondary metabolites which are produced by plants as side products of certain physiological reactions and are of no use for the plant itself. These components have been reported for their medicinal properties. In this review, we have mentioned some antibacterial, antifungal, and wound healing properties of A. catechu with its known bioactive components. The aim of this review article is, to enlist the possible potent bioactive components of the plant, against pathogenic microbes that can replace the use of chemicals and synthetic antibiotics for the treatment of skin infections and other diseases.